2020
DOI: 10.1007/s11920-020-01208-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Brain Mechanisms of Reactive Aggression

Abstract: Purpose of Review To review the current literature on biobehavioral mechanisms involved in reactive aggression in a transdiagnostic approach. Recent Findings Aggressive reactions are closely related to activations in the brain’s threat circuitry. They occur in response to social threat that is experienced as inescapable, which, in turn, facilitates angry approach rather than fearful avoidance. Provocation-induced aggression is strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 104 publications
(123 reference statements)
10
82
0
Order By: Relevance
“…The present results thus indicate that the striatum is not only sensitive to status signals (Zink et al, 2008;Zerubavel et al, 2015) and competitive outcomes (Qu et al, 2017), but also differentiates between individuals differing in status during decisions to aggress. Our findings are in line with the hypothesized role of the striatum in retaliatory aggression (Chester, 2017;Bertsch et al, 2020), and concur with metaanalytic findings demonstrating increased striatal activity when individuals deliver harsher punishments to unfair co-players (Gabay et al, 2014). Therefore, our data bridge animal and human research in showing that the hippocampus and striatum are involved in the relational processing of social dominance signals.…”
Section: Neural Representations Of Competitive Status During Punishment Selectionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present results thus indicate that the striatum is not only sensitive to status signals (Zink et al, 2008;Zerubavel et al, 2015) and competitive outcomes (Qu et al, 2017), but also differentiates between individuals differing in status during decisions to aggress. Our findings are in line with the hypothesized role of the striatum in retaliatory aggression (Chester, 2017;Bertsch et al, 2020), and concur with metaanalytic findings demonstrating increased striatal activity when individuals deliver harsher punishments to unfair co-players (Gabay et al, 2014). Therefore, our data bridge animal and human research in showing that the hippocampus and striatum are involved in the relational processing of social dominance signals.…”
Section: Neural Representations Of Competitive Status During Punishment Selectionsupporting
confidence: 90%
“…The key question that we addressed here is which role these neurocognitive processes play in status-dependent aggression. We reasoned that the neural substrate of status-processing and aggression should show some degree of overlap, be it in subcortical structures assumed to generate aggressive impulses such as the amygdala (da Cunha-Bang et al, 2017;Buades-Rotger and Krämer, 2018), in those linked with retaliation such as the VS (Buades-Rotger, Brunnlieb, et al, 2016;Chester and DeWall, 2016), and/or in areas suggested to regulate aggression such as the vmPFC (Buades-Rotger et al, 2019;Bertsch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of impulsive aggression (or constructs closely linked to it) has repeatedly been associated with heightened amygdala reactivity in the context of angry faces (63,64,(68)(69)(70), fearful faces (11), and provocations in the PSAP (67, 71). A recent review suggests that brain regions involved in threat sensitivity (amygdala, hypothalamus, PAG) and frustrative non-reward (amygdala, VS, caudate nucleus) represent 'activation conditions' and regions involved in cognitive control (PFC, insula, inferior parietal lobules) represent a 'regulating condition' for impulsive aggression (72). This is in line with another review of nine fMRI TAP studies concluding that a neural circuitry mediating emotional reactivity and cognitive control is implicated in reactive aggression (73), although a meta-analysis revealed that the left postcentral gyrus was the only region consistently activated across these TAP studies (74).…”
Section: Functional Neuroimaging Evidence For Brain Circuit Involvementmentioning
confidence: 99%
“…In this meta-analysis, we followed Berkowitz' (1989) proposition suggesting that withholding/removing an expected reward would enhance emotional arousal, which further increase the risk for reactive aggression. Given that several psychopathologies may exhibit enhanced risk for frustration and reactive aggression (Bertsch et al, 2020;Leibenluft, 2017), its implication for clinical population are also discussed.…”
Section: Integrative Neurobiological Model Of Frustration-aggression Sequencementioning
confidence: 99%
“…In the last decade, frustration has been thought to be implicated in several psychopathologies that are at risk for aggressive behaviors (e.g., irritability, CD/ASPD, see (Bertsch, Florange, & Herpertz, 2020;Blair, 2010b;Harenski & Kiehl, 2010;Leibenluft, 2017)).…”
Section: Introductionmentioning
confidence: 99%